Cationic polymer nano-microsphere emulsion, preparation method and application of cationic polymer nano-microsphere emulsion in antifibrillation of lyocell knitted fabric

The hydrophobic polymer film is formed through electrostatic adsorption and high-temperature baking of cationic polymer nano-microsphere emulsion, which solves the problems of improving anti-fibrillation performance of Lécel fabrics and maintaining the mechanical properties of fibers, and achieves efficient anti-fibrillation treatment, avoiding the problems of "yellowing" of fibers and formaldehyde release.

CN119505060APending Publication Date: 2025-02-25QINGDAO UNIV

Patent Information

Application Number
CN202411671319.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the mechanical and breathable properties of the fibers while improving the antifibrillation performance of the Lycel fabric, and there are problems such as "yellowing" of the fibers and formaldehyde release.

Method used

The cationic polymer nano-microsphere emulsion is prepared by soap-free emulsion polymer polymer films, and electrostatic adsorption and high-temperature baking are used to form a hydrophobic polymer film to enhance the hydrophobicity of the fibers and reduce the tendency of fibrillation.

Benefits of technology

The antifibrillation performance of Lycel fibers is significantly improved, the mechanical and breathable properties of the fibers are maintained, the problems of "yellowing" and formaldehyde release are avoided, and the process steps are simplified and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505060A_ABST
    Figure CN119505060A_ABST
Patent Text Reader

Abstract

The invention discloses a cationic polymer nano-microsphere emulsion which is prepared from the following raw materials in percentage by mass through a soap-free emulsion polymerization method: 10% of a hydrophobic monomer; 0.2%-2% of a cationic monomer; 0.02% to 0.14% of a cationic water-soluble azo initiator; and the balance of deionized water. The invention relates to a preparation method and application thereof in antifibrillation of lyocell knitted fabric. According to the method, during high-temperature baking, the adsorbed nanospheres can be diffused into a discontinuous film, hydrophobic chain segments of the nanospheres are exposed in air, so that the surfaces of the hydrophilic fibers are changed into hydrophobic surfaces, the hydrophobicity of the fibers is enhanced, and the swelling degree of the fibers is reduced due to the hydrophobicity. Under the action of wet state and friction, the fibrillation tendency of the lyocell fiber is obviously prevented. According to the method, the anti-fibrillation performance of the lyocell fiber is obviously enhanced, meanwhile, the influence on the mechanical property of the fiber is small, in addition, the process steps are obviously reduced, and the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of textile dyeing and finishing, and particularly relates to a cationic polymer nano-microsphere emulsion, a preparation method and application thereof in anti-fibrillation of lyocell knitted fabrics. Background Art

[0002] Lyocell fiber is a regenerated cellulose fiber made from rapidly renewable wood, dissolved in NMMO solvent and prepared by dry-jet wet spinning. It is known as the "green fiber of the 21st century" for its environmentally friendly production process, biodegradability and non-toxicity to the environment. Lyocell fiber materials have significant advantages in environmental protection and sustainability, showing broad market application prospects.

[0003] However, the fibrillation problem of Lyocell fiber in yarn, knitted fabrics, towels, etc. has not been effectively solved, and this problem has become a bottleneck restricting its further market expansion. The fibrillation phenomenon of Lyocell fiber refers to the phenomenon that giant fibrils are split on the surface of the main fiber along the length of the fiber, and the giant fibrils continue to split to produce more small and uneven microfibrils. The occurrence of the fibrillation phenomenon of Lyocell fiber is closely related to its own structure. The inside of Lyocell fiber is a skin-core structure, the skin layer is thin, about 0.2-1μm, and the skin layer is composed of highly crystallized cellulose fibrils and nano-voids. Its cellulose macromolecules are highly oriented in the longitudinal direction and have strong binding force, while the transverse binding force is weak, which will cause the anisotropy of Lyocell fiber in different directions. This difference will be more obvious after the Lyocell fiber is swollen in water, and the transverse force between the cellulose macromolecular chains is reduced, so Lyocell fiber is prone to severe fibrillation under mechanical friction under wet conditions. Fibrillation can cause "frost" to appear on the dyed fabric, making the color lighter and affecting the uniformity of the appearance. When the fabric fibrillation is serious, problems such as "pilling" may even occur on the fabric surface, greatly reducing the appearance quality and durability of the product.

[0004] In order to control the fibrillation of lyocell fibers, many methods have been developed so far, including chemical crosslinking of fibers, enzyme treatment, and resin finishing. For example, crosslinking between fibrils is carried out using crosslinking agents and multifunctional reactive dyes. In the article "Study on Anti-fibrillation of Lyocell Fibers", Lenzing, Austria, introduced that dichloroisotriazine reactive dyes can be used to reduce the fibrillation tendency of lyocell fabrics by crosslinking the hydroxyl groups of cellulose molecular chains. Patent CN116716730A discloses a process for impregnating lyocell knitted fabrics to prevent fibrillation. A low-temperature, environmentally friendly, and efficient fibrillation prevention and control process is developed using a cationic crosslinking agent containing a diepoxy group under low temperature conditions. Patent CN115772811A discloses a cold rolling batch dyeing process for preventing fibrillation of lyocell fibers. The interaction of lyocell cellulose chains is enhanced by chemical crosslinking of anti-fibrillation treatment agents and multi-active reactive dyes to achieve control of fiber fibrillation. Polycarboxylic acids, such as citric acid (CA) and 1,2,3,4-butanetetracarboxylic acid (BTCA), are considered promising green and efficient crosslinkers by establishing ester bonds between hydroxyl groups. Dimethylol dihydroxyethylene urea (DMDHEU) is a product of formaldehyde, glyoxal and urea, and is also an effective commercial crosslinker for controlling the fibrillation of lyocell fibers. Patent CN1077184C discloses a method for reducing the fibrillation tendency and degree of cellulose fabrics, using resin finishing, and achieving the purpose of reducing fiber fibrillation through steps such as heating curing, washing, and drying.

[0005] In summary, although the above method can reduce the fibrillation tendency of lyocell fiber to a certain extent, the fiber chemical crosslinking generally causes damage to the fiber, and excessive crosslinking can greatly reduce the mechanical properties of the fiber. Some other crosslinking treatment methods can affect the subsequent processing of lyocell fiber, such as polycarboxylic acid citric acid CA, which is easy to cause "yellowing" phenomenon during high temperature curing, and there is a formaldehyde release problem in resin finishing. In general, most of the methods for controlling the fibrillation of lyocell fiber at present still have problems such as formaldehyde release, large strength loss, low practicality, cumbersome process flow, high cost, and small scope of application. Therefore, how to improve the anti-fibrillation performance of lyocell fabric while maintaining the good mechanical properties and air permeability of lyocell fiber, and will not cause the phenomenon of fiber "yellowing" and formaldehyde release, and have the advantages of simple processing procedure, low cost, and low chemical consumption, which has become a difficult problem that technicians in the field of anti-fibrillation of lyocell fabric need to solve. Summary of the invention

[0006] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to provide a cationic polymer nano-microsphere emulsion, a preparation method and application thereof in the fibrillation resistance of lyocell knitted fabrics, which can improve the anti-fibrillation performance of lyocell fabrics while maintaining the good mechanical properties and air permeability of lyocell fibers and will not cause problems such as "yellowing" of the fibers and formaldehyde release.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a cationic polymer nano-microsphere emulsion is prepared by a soap-free emulsion polymerization method using the following raw materials in mass percentage:

[0008]

[0009] The cationic polymer nanosphere emulsion mentioned above, the cationic polymer forming nanospheres in the emulsion has the general structural formula:

[0010]

[0011] Wherein, R1 is selected from any one of benzene, acyloxymethyl, acyloxyethyl, acyloxybutyl, R2 is selected from any one of acyloxymethyl and acyloxyoctadecyl, R3 is selected from any one of H or methyl, and R4 is selected from any one of acyloxyethyl or p-methylenebenzene. In the above cationic polymer nanosphere emulsion, the molar ratio of the cationic monomer to the hydrophobic monomer is 1:10-210.

[0012] In the above-mentioned cationic polymer nanosphere emulsion, the hydrophobic monomer is any one or more of styrene, methyl methacrylate, butyl acrylate, octadecyl methacrylate, ethyl acrylate, and methyl methacrylate; the cationic monomer is any one or more of methacryloyloxyethyl trimethyl ammonium chloride and p-vinyl benzyl trimethyl ammonium chloride; and the cationic water-soluble azo initiator is any one or two of azobisisobutylamidine hydrochloride and azobisisobutylimidazoline hydrochloride.

[0013] The cationic polymer nano-microsphere emulsion mentioned above has a particle size of 55-150 nm.

[0014] A method for preparing a cationic polymer nanosphere emulsion comprises the following steps:

[0015] (1) Add a certain amount of deionized water into a four-necked flask equipped with a stirrer, a condenser reflux tube, and a nitrogen inlet device, and stir;

[0016] (2) Add 0.2% to 2% by weight of cationic monomer into a four-necked flask and stir for 15 to 60 minutes.

[0017] (3) 10% by weight of a hydrophobic monomer was added to a four-necked flask, and after sufficient stirring, the heating temperature was adjusted to 78-82°C at a heating rate of 2°C / min;

[0018] (4) Add 0.02%-0.14% by weight of a cationic water-soluble azo initiator, control the drop rate, and react at 80° C. for a certain period of time to obtain a cationic polymer nanosphere emulsion.

[0019] Application of cationic polymer nano-microsphere emulsion in anti-fibrillation of lyocell knitted fabrics comprises the following steps:

[0020] 1. Washing and degreasing of lyocell knitted fabric:

[0021] (1) At room temperature, add 3-10 g / L of Dye Bath Treasure and 0.5-3 g / L of degreasing agent to deionized water and stir for 20 minutes to prepare a degreasing solution for later use;

[0022] (2) Add lyocell knitted fabric, bath ratio 1:15, heat the degreasing solution at a heating rate of 5°C / min, heat to 80°C and treat for 15-60min;

[0023] (3) After the degreasing solution is cooled to 40°C, take out the lyocell knitted fabric;

[0024] 2. Impregnation modification treatment:

[0025] (4) preparing a certain mass fraction of the cationic polymer nanosphere emulsion according to any one of claims 1 to 5 at room temperature as a modified treatment liquid for standby use;

[0026] (5) immersing the lyocell knitted fabric in the cationic polymer nanosphere emulsion prepared in step (4) at a bath ratio of 1:10, adjusting the pH of the modified treatment solution to 4-11, heating the solution to 30° C., immersing the solution for 15-60 min, and then draining the solution to take out the lyocell knitted fabric;

[0027] (6) dehydrating and drying the lyocell knitted fabric after the impregnation modification treatment;

[0028] 3. High temperature baking treatment:

[0029] (7) The lyocell knitted fabric obtained in step (6) is subjected to a high temperature baking treatment, the baking temperature is 120-180° C., and the treatment time is 5 min.

[0030] In the above application, in the step (4), the mass fraction of the cationic polymer nanosphere emulsion is 5-80 g / L.

[0031] In the above application, in step (5), the pH of the modified treatment liquid is adjusted to 5.

[0032] In the above application, in step (7), the baking temperature is 150°C.

[0033] The cationic polymer nano-microsphere emulsion, preparation method and application thereof in anti-fibrillation of lyocell knitted fabrics have the advantages that the cationic polymer nano-spheres are adsorbed onto the negatively charged lyocell fiber surface under the induction of electrostatic force, and the adsorbed nano-spheres can be diffused into a discontinuous film during high-temperature baking, and the hydrophilic fiber surface is changed into a hydrophobic surface by exposing the hydrophobic segments of the nano-spheres to the air, thereby enhancing the fiber hydrophobicity, and this hydrophobicity reduces the fiber swelling degree. Under wet state and friction, the fibrillation tendency of the lyocell fiber is significantly prevented. The anti-fibrillation performance of the lyocell fiber is obviously enhanced, and the mechanical property of the fiber is less affected simultaneously, and the process steps are obviously reduced in addition, thereby reducing the cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The diagram is a mechanism diagram of the reaction between the cationic polymer nanospheres and the lyocell fibers of the present invention;

[0035] Figure 2 is the particle size distribution diagram of cationic polymer nanospheres in the emulsion;

[0036] Figure 3 This is a SEM electron microscope image of the Lyocell knitted fabric obtained in Example 1 after being fibrillated and washed;

[0037] Figure 4 This is a SEM electron microscope image of the fibers of the Lyocell knitted fabric prepared in the comparative example after being fibrillated and washed;

[0038] Figure 5 This is a FE-SEM high-resolution electron microscope image of a magnified part of the fiber of the Lyocell knitted fabric prepared in Example 1 after being fibrillated and washed;

[0039] Figure 6 This is a FE-SEM high-resolution electron microscope image of a partially enlarged fiber of a lyocell knitted fabric prepared in a comparative example after being fibrillated and washed;

[0040] Figure 7 The water contact angle test diagram of the surface of the lyocell knitted fabric prepared in Example 1 and the comparative example;

[0041] Figure 8 The figure is a test diagram of the mechanical properties of the lyocell knitted surface prepared in Example 1 and the comparative example;

[0042] Fig. 9 This is a SEM electron microscope image of the Lyocell knitted fabric obtained in Example 2 after being fibrillated and washed;

[0043] Fig.10 This is a SEM electron microscope image of the Lyocell knitted fabric obtained in Example 3 after being fibrillated and washed;

[0044] Fig.11 This is a SEM electron microscope image of the Lyocell knitted fabric obtained in Example 4 after being fibrillated and washed;

[0045] Fig.12 This is a SEM electron microscope image of the Lyocell knitted fabric obtained in Example 5 after being fibrillated and washed;

[0046] Fig.13 This is a SEM electron microscope image of the Lyocell knitted fabric prepared in Example 6 after being fibrillated and washed. DETAILED DESCRIPTION

[0047] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0048] In the present invention, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the attached drawings; while "inside" and "outside" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order. The term "plurality" means "two or more".

[0049] A cationic polymer nano-microsphere emulsion is prepared by a soap-free emulsion polymerization method using the following raw materials in percentage by mass: 10% hydrophobic monomer; 0.2%-2% cationic monomer; 0.02%-0.14% cationic water-soluble azo initiator; and the balance deionized water.

[0050] Wherein, the hydrophobic monomer is any one or more of styrene, methyl methacrylate, butyl acrylate, octadecyl methacrylate, ethyl acrylate, and methyl methacrylate; the cationic monomer is any one or more of methacryloyloxyethyl trimethyl ammonium chloride and p-vinyl benzyl trimethyl ammonium chloride; the cationic water-soluble azo initiator is any one or two of azobisisobutylamidine hydrochloride and azobisisobutylimidazoline hydrochloride. The molar ratio of the cationic monomer to the hydrophobic monomer is 1:10-210. Figure 2 As shown, the particle size of the cationic polymer nanospheres in the emulsion is 55-150 nm.

[0051] The preparation method of the cationic polymer nano-microsphere emulsion of the present invention comprises the following steps:

[0052] (1) Add a certain amount of deionized water into a four-necked flask equipped with a stirrer, a condenser reflux tube, and a nitrogen inlet device, and stir;

[0053] (2) Add 0.2% to 2% by weight of cationic monomer into a four-necked flask and stir for 15 to 60 minutes.

[0054] (3) 10% by weight of a hydrophobic monomer was added to a four-necked flask, and after sufficient stirring, the heating temperature was adjusted to 78-82°C at a heating rate of 2°C / min;

[0055] (4) Add 0.02%-0.14% by weight of a cationic water-soluble azo initiator, control the drop rate, and react at 80° C. for a certain period of time to obtain a cationic polymer nanosphere emulsion.

[0056] The reaction process of synthesizing cationic polymer nanospheres by soap-free emulsion polymerization of the present invention is as follows:

[0057]

[0058] The general structural formula of the cationic polymer that finally forms nanospheres is:

[0059]

[0060] Among them, R1 is selected from any one of benzene, acyloxymethyl, acyloxyethyl, and acyloxybutyl, R2 is selected from any one of acyloxymethyl and acyloxyoctadecyl, R3 is selected from any one of H or methyl, and R4 is selected from any one of acyloxyethyl or p-methylenebenzene.

[0061] In the process of preparing the cationic polymer nanosphere emulsion, in order to control the progress of the polymerization reaction and the performance of the product, the quality and stability of the polymer are improved. The preparation process first adds the cationic monomer, then the hydrophobic monomer, and finally the cationic water-soluble azo initiator. As is well known, soap-free emulsion polymerization refers to an emulsion polymerization process in which no emulsifier is added or only a trace emulsifier (whose concentration is less than the critical micelle concentration CMC) is added during the reaction, but an initiator or a polar comonomer is used to chemically link the polar or ionizable groups to the polymer, so that the polymer itself has surface activity.

[0062] Since the outer layer of the polymer particles synthesized by emulsion polymerization is a hydrophilic material and the inner layer is a hydrophobic material, the cationic monomer is added first to allow the cationic monomer to be evenly distributed in the synthetic solution. Cationic monomers such as methacryloyloxyethyl trimethylammonium chloride (DMC) introduce positive charges during the polymerization process, so that the surface of the polymer particles has a certain charge. This helps to enhance the stability of the polymer particles and prevent agglomeration between particles.

[0063] The addition of hydrophobic monomers can be adsorbed on the surface of the particles to form a hydrophobic layer, thereby making the surface of the particles more stable and reducing mutual adsorption and agglomeration between the particles.

[0064] Initiators play a role in starting the polymerization reaction in emulsion polymerization. They generate free radicals through decomposition, triggering a chain reaction between monomer molecules to form polymers. Adding cationic monomers and hydrophobic monomers first and initiators last can make the surface of polymer particles charged and form a hydrophobic layer, which helps to better control the progress of the polymerization reaction and the performance of the product when the initiator is added later.

[0065] The application of the cationic polymer nano-microsphere emulsion prepared by the above method in the anti-fibrillation of lyocell knitted fabrics comprises the following steps:

[0066] 1. Washing and degreasing of lyocell knitted fabric:

[0067] (1) At room temperature, add 3-10 g / L of Dye Bath Treasure and 0.5-3 g / L of degreasing agent to deionized water, stir for 20 minutes to prepare a degreasing solution for later use;

[0068] (2) Add lyocell knitted fabric, bath ratio 1:15, heat the degreasing solution at a heating rate of 5°C / min, heat to 80°C and treat for 15-60min;

[0069] (3) After the degreasing solution is cooled to 40°C, take out the lyocell knitted fabric;

[0070] 2. Impregnation modification treatment:

[0071] (4) preparing a cationic polymer nanosphere emulsion with a mass fraction of 5-80 g / L at room temperature as a modified treatment liquid for standby use;

[0072] (5) immersing the lyocell knitted fabric in the cationic polymer nanosphere emulsion prepared in step (4) at a bath ratio of 1:10, adjusting the pH of the modified treatment solution to 4-11, heating the solution to 30° C., immersing the solution for 15-60 min, and then draining the solution to take out the lyocell knitted fabric;

[0073] (6) dehydrating and drying the lyocell knitted fabric after the impregnation modification treatment;

[0074] 3. High temperature baking treatment:

[0075] (7) The lyocell knitted fabric obtained in step (6) is subjected to a high temperature baking treatment, the baking temperature is 120-180° C., and the treatment time is 5 min.

[0076] like Figure 1 As shown, the mechanism of the cationic polymer nano-microsphere emulsion used for the anti-fibrillation of lyocell knitted fabrics is as follows: the cationic polymer emulsion is synthesized by emulsion polymerization technology and the lyocell fabric is impregnated, the quaternary ammonium group in the cationic polymer structure will show strong positive charge in water, and the surface of the lyocell fiber will show negative charge in water, under the induction of electrostatic attraction, the surface of the lyocell fiber will adsorb the cationic nano-microspheres, which will neutralize the positive and negative charges on the fiber surface; after high-temperature baking, the microspheres adsorbed on the fiber surface will melt and spread to form a polymer film, so that the hydrophobic groups (such as benzene rings and ester groups) in the internal structure of the microspheres are exposed, and at this time, the methyl and methylene segments in the polymer structure will also face the air end, and the fiber surface groups will change (from hydrophilic hydroxyl groups to hydrophobic methyl, methylene, benzene rings, ester groups, etc.), so that the fiber surface as a whole presents high hydrophobicity, which will prevent water molecules from entering the fiber interior, reduce swelling, and further control the generation of fiber fibrillation. At the same time, the smaller particle size of cationic polymer nanospheres provides a larger specific surface area, ensuring that they can provide more adsorption quantity for the surface of lyocell fibers during the reaction with lyocell fibers, making the formed polymer film more uniform, and also providing more hydrophobic groups, enhancing the hydrophobic properties of the surface of lyocell fibers, thereby improving the anti-fibrillation effect.

[0077] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0078] It should be noted that g / L in the examples is a basic unit in the field of textile dyeing and finishing, such as "10 g / L of cationic polymer emulsion" means that the amount of cationic polymer emulsion added to 1L of water is 10 g, and the following drying, baking and washing are conventional methods in the art. The cationic polymer emulsion in the invention is synthesized independently by this laboratory. The fibrillation washing process in the following examples and comparative examples refers to the ISO 6330 2012 washing standard, i.e., the standard procedure for household washing and drying.

[0079] Example 1

[0080] A cationic polymer nanosphere emulsion is prepared by a soap-free emulsion polymerization method using the following raw materials in mass percentage: 8% styrene, 2% butyl acrylate (total 10%); 0.3% methacryloyloxyethyl trimethylammonium chloride; 0.04% azobisisobutylamidine hydrochloride; the balance is deionized water. In this embodiment, the amounts of styrene and butyl acrylate in the synthesized cationic polymer nanosphere emulsion are 8g and 2g, respectively. The molar ratio of the cationic monomer to the hydrophobic monomer is 1:150. The particle size of the cationic polymer nanospheres in the emulsion is 88nm.

[0081] The preparation method thereof comprises the following steps:

[0082] (1) Add a certain amount of deionized water into a four-necked flask equipped with a stirrer, a condenser reflux tube, and a nitrogen inlet device, and stir;

[0083] (2) Add 0.3% by mass of methacryloyloxyethyl trimethyl ammonium chloride into a four-necked flask and stir for 30 minutes.

[0084] (3) 8% by weight of styrene and 2% by weight of butyl acrylate were added to a four-necked flask, and after sufficient stirring, the heating temperature was adjusted to 80° C. at a heating rate of 2° C. / min;

[0085] (4) Add 0.04% by weight of a cationic water-soluble azo initiator, control the drop rate, and react at 80° C. for a certain period of time to obtain a cationic polymer nanosphere emulsion.

[0086] The application of the cationic polymer nano-microsphere emulsion in the anti-fibrillation of lyocell knitted fabrics comprises the following steps:

[0087] 1. Washing and degreasing of lyocell knitted fabric:

[0088] (1) At room temperature, add 5 g / L of Dye Bath Treasure and 1.5 g / L of degreasing agent to deionized water and stir for 20 min to prepare a degreasing solution for later use;

[0089] (2) Add undyed lyocell knitted fabric, with a bath ratio of 1:15, and heat the degreasing solution at a heating rate of 5°C / min to 80°C for 30min;

[0090] (3) After the degreasing solution is cooled to 40°C, take out the lyocell knitted fabric;

[0091] 2. Impregnation modification treatment:

[0092] (4) preparing a cationic polymer nanosphere emulsion with a mass fraction of 10 g / L at room temperature as a modified treatment liquid for later use;

[0093] (5) immersing the lyocell knitted fabric in the cationic polymer nanosphere emulsion prepared in step (4) at a bath ratio of 1:10, adjusting the pH of the modified treatment solution to 5, raising the temperature to 30° C., immersing for 30 minutes, draining the solution, and taking out the lyocell knitted fabric;

[0094] (6) dehydrating and drying the lyocell knitted fabric after the impregnation modification treatment;

[0095] 3. High temperature baking treatment:

[0096] (7) The lyocell knitted fabric obtained in step (6) is subjected to a high-temperature baking treatment at a temperature of 150° C. for a treatment time of 5 min.

[0097] Comparative Example

[0098] The difference between the comparative example and Example 1 is that the anti-fibrillation treatment liquid for the lyocell knitted fabric does not contain the cationic polymer nano-microsphere emulsion, and the remaining steps and parameters are the same as those of Example 1. The main steps are as follows:

[0099] (1) Washing and degreasing the undyed lyocell knitted fabric;

[0100] (2) Prepare a treatment liquid without cationic polymer nanosphere emulsion at a bath ratio of 1:10 at room temperature, immerse the degreased Lyocell knitted fabric in the treatment liquid and heat it to 30°C for 30 minutes, drain the liquid and take it out;

[0101] (3) The treated lyocell knitted fabric is dehydrated, dried, and finally subjected to high-temperature baking treatment at a temperature of 150° C. for 5 minutes.

[0102] Example 2

[0103] The same parts of this embodiment as those of embodiment 1 are not described in detail. The difference is that the amounts of styrene and butyl acrylate in the cationic polymer nanosphere emulsion synthesized in this embodiment are 7 g and 3 g, respectively.

[0104] Example 3

[0105] The same parts of this embodiment as those of embodiment 1 are not described in detail. The difference is that the amounts of styrene and butyl acrylate in the cationic polymer nanosphere emulsion synthesized in this embodiment are 6 g and 4 g, respectively.

[0106] Example 4 (Comparative Example 2)

[0107] The difference between the process of this embodiment and the process of embodiment 1 is that the amount of cationic polymer emulsion used is 40 g / L, and other operating conditions are the same as those of embodiment 1.

[0108] Example 5 (Comparative Example 3)

[0109] The difference between the process of this embodiment and the process of embodiment 1 is that the pH value of the treatment solution during the immersion treatment is 8, and the other operating conditions are the same as those of embodiment 1.

[0110] Example 6 (Comparative Example 4)

[0111] The difference between the process of this embodiment and the process of embodiment 1 is that the pH value of the treatment solution during the immersion treatment is 11, and the other operating conditions are the same as those of embodiment 1.

[0112] Example 7

[0113] A cationic polymer nanosphere emulsion is prepared by a soap-free emulsion polymerization method using the following raw materials in mass percentage: 7% styrene, 3% butyl acrylate (total 10%); 0.2% methacryloyloxyethyl trimethylammonium chloride; 0.02% azobisisobutylamidine hydrochloride; the balance is deionized water. In this embodiment, the amounts of styrene and butyl acrylate in the synthesized cationic polymer nanosphere emulsion are 7g and 3g, respectively. The molar ratio of the cationic monomer to the hydrophobic monomer is 1:10. The particle size of the cationic polymer nanosphere in the emulsion is 55nm.

[0114] The preparation method thereof comprises the following steps:

[0115] (1) Add a certain amount of deionized water into a four-necked flask equipped with a stirrer, a condenser reflux tube, and a nitrogen inlet device, and stir;

[0116] (2) Add 0.2% by mass of methacryloyloxyethyl trimethyl ammonium chloride into a four-necked flask and stir for 15 minutes.

[0117] (3) 7% by weight of styrene and 3% by weight of butyl acrylate were added to a four-necked flask, and after sufficient stirring, the heating temperature was adjusted to 80° C. at a heating rate of 2° C. / min;

[0118] (4) Add 0.02% by weight of a cationic water-soluble azo initiator, control the drop rate, and react at 80° C. for a certain period of time to obtain a cationic polymer nanosphere emulsion.

[0119] The application of the cationic polymer nano-microsphere emulsion in the anti-fibrillation of lyocell knitted fabrics comprises the following steps:

[0120] 1. Washing and degreasing of lyocell knitted fabric:

[0121] (1) At room temperature, add 3 g / L of Dye Bath Treasure and 3 g / L of degreasing agent to deionized water and stir for 20 min to prepare a degreasing solution for later use;

[0122] (2) Add undyed lyocell knitted fabric, with a bath ratio of 1:15, and heat the degreasing solution at a heating rate of 5°C / min to 80°C for 15min;

[0123] (3) After the degreasing solution is cooled to 40°C, take out the lyocell knitted fabric;

[0124] 2. Impregnation modification treatment:

[0125] (4) Prepare a cationic polymer nanosphere emulsion with a mass fraction of 5 g / L at room temperature as a modified treatment liquid for later use;

[0126] (5) immersing the lyocell knitted fabric in the cationic polymer nanosphere emulsion prepared in step (4) at a bath ratio of 1:10, adjusting the pH of the modified treatment solution to 11, heating the solution to 30° C., immersing the solution for 15 min, and then draining the solution to take out the lyocell knitted fabric;

[0127] (6) dehydrating and drying the lyocell knitted fabric after the impregnation modification treatment;

[0128] 3. High temperature baking treatment:

[0129] (7) The lyocell knitted fabric obtained in step (6) is subjected to a high-temperature baking treatment, the baking temperature is 120° C., and the treatment time is 5 min.

[0130] Example 8

[0131] A cationic polymer nanosphere emulsion is prepared by a soap-free emulsion polymerization method using the following raw materials in mass percentage: 6% styrene, 4% butyl acrylate (total 10%); 2% methacryloyloxyethyl trimethylammonium chloride; 0.14% azobisisobutylamidine hydrochloride; the balance is deionized water. In this embodiment, the amounts of styrene and butyl acrylate in the synthesized cationic polymer nanosphere emulsion are 6g and 4g, respectively. The molar ratio of the cationic monomer to the hydrophobic monomer is 1:210. The particle size of the cationic polymer nanosphere in the emulsion is 150nm.

[0132] The preparation method thereof comprises the following steps:

[0133] (1) Add a certain amount of deionized water into a four-necked flask equipped with a stirrer, a condenser reflux tube, and a nitrogen inlet device, and stir;

[0134] (2) Add 0.3% by mass of methacryloyloxyethyl trimethyl ammonium chloride into a four-necked flask and stir for 60 minutes.

[0135] (3) 6% by mass of styrene and 4% by mass of butyl acrylate were added to a four-necked flask, and after sufficient stirring, the heating temperature was adjusted to 80° C. at a heating rate of 2° C. / min;

[0136] (4) Add 0.14% by weight of a cationic water-soluble azo initiator, control the drop rate, and react at 80° C. for a certain period of time to obtain a cationic polymer nanosphere emulsion.

[0137] The application of the cationic polymer nano-microsphere emulsion in the anti-fibrillation of lyocell knitted fabrics comprises the following steps:

[0138] 1. Washing and degreasing of lyocell knitted fabric:

[0139] (1) At room temperature, add 10 g / L of Dye Bath Treasure and 0.5 g / L of degreasing agent to deionized water and stir for 20 min to prepare a degreasing solution for later use;

[0140] (2) Add undyed lyocell knitted fabric, with a bath ratio of 1:15, and heat the degreasing solution at a heating rate of 5°C / min to 80°C for 60min;

[0141] (3) After the degreasing solution is cooled to 40°C, take out the lyocell knitted fabric;

[0142] 2. Impregnation modification treatment:

[0143] (4) Prepare a cationic polymer nanosphere emulsion with a mass fraction of 80 g / L at room temperature as a modified treatment liquid for later use;

[0144] (5) immersing the lyocell knitted fabric in the cationic polymer nanosphere emulsion prepared in step (4) at a bath ratio of 1:10, adjusting the pH of the modified treatment solution to 4, heating the solution to 30° C., immersing the solution for 60 min, draining the solution, and taking out the lyocell knitted fabric;

[0145] (6) dehydrating and drying the lyocell knitted fabric after the impregnation modification treatment;

[0146] 3. High temperature baking treatment:

[0147] (7) The lyocell knitted fabric obtained in step (6) is subjected to a high-temperature baking treatment, the baking temperature is 180° C., and the treatment time is 5 min.

[0148] Example 9

[0149] The difference between the process of this embodiment and the process of embodiment 1 is that the hydrophobic monomers styrene and butyl acrylate are replaced by octadecyl methacrylate, and the other operating conditions are the same as those of embodiment 1.

[0150] The performance test results of the cationic polymer nano-microsphere emulsion used in the lyocell knitted fabric in terms of anti-fibrillation, mechanical properties, air permeability, etc. are as follows:

[0151] 1. About anti-fibrillation performance:

[0152] like Figure 3 , 4As shown in Figures 5 and 6, the electron microscope images of the lyocell knitted fabrics obtained in Example 1 and the comparative example after being washed with fibrillated water show that the knitted fabric of the comparative example that has not been treated with the cationic polymer emulsion has obvious fibrillation after washing, while the fibrillation phenomenon on the fiber surface of Example 1 is significantly reduced after being treated with the cationic polymer emulsion. Figure 3 and Figure 5 High-resolution electron microscopy images clearly show the fibrils generated on the fiber surface before and after treatment. Figure 3 It can be seen that there are few fibrils on the fiber surface of the Lyocell fabric after microsphere treatment. Figure 4 The untreated lyocell fabric has many fibrils on its fiber surface. Figure 4 , Figure 6 It was found that the untreated fiber had a verified fibrillation phenomenon due to the rupture of the cortex, while the treated fiber had a smooth surface covered with an uneven thin coating of nano-microspheres. The polymer film formed protected the fiber and subdued the tiny fibrils on the fiber surface, so no obvious fibrillation occurred on the fiber surface. Therefore, it is precisely because of the appearance of these coatings on the fiber surface that Lyocell fiber has excellent anti-fibrillation properties.

[0153] The Zeta potential of the surface of the lyocell knitted fabrics prepared under different pH conditions in Example 1 and the comparative example is as follows:

[0154]

[0155]

[0156] Since cationic nanospheres are adsorbed on the negatively charged surface of Lyocell fibers through electrostatic interaction, "charge neutralization" occurs, so that the "negative charge centers" on the fiber surface due to the damage of the fiber surface and the "oxidation" of the groups are largely neutralized, reducing the fibrillation behavior caused by the "negative charge centers" on the fiber surface. The method of modifying Lyocell fibers with cationic polymer emulsion has little effect on the mechanical properties of the fibers. At the same time, the formation of the fiber surface film improves the strength of the fiber cortex, thereby reducing the fibrillation behavior caused by the rupture of the fiber cortex.

[0157] It can be seen from the above table that the untreated lyocell fabric always maintains negative charge. After being treated with PSBD cationic emulsion, the fabric is positively charged under strong acidic conditions and still negatively charged under weakly acidic and alkaline conditions, but the overall negative charge on the fiber surface is reduced, which indicates that the negatively charged groups on the surface of the lyocell fiber are neutralized with the positively charged groups of the nano-microspheres themselves.

[0158] Figure 7 The following table shows the test results of hydrophilicity and lateral swelling degree of the fabrics obtained in Example 1 and the comparative example. Figure 7Example 1 is the treated result, and the comparative example is the untreated result. Figure 7 It can be seen that the untreated lyocell fiber has good hydrophilicity and the wetting time is about 0.3s. After solidification into a film, the fiber shows high hydrophobicity, and also causes the change of the fiber's swelling property in water. Example 1 in the following table is a sample after modification, and the comparative example is an untreated sample.

[0159]

[0160] As can be seen from the table above, the lateral swelling rate of untreated lyocell yarn in water is about 24%, and the swelling rate of the modified fabric after heat treatment in water is significantly reduced to 7%. This is because the cationic polymer nanospheres change the chemical groups on the fiber surface through adsorption, heat treatment and other processes and form a highly hydrophobic polymer film on the fiber surface, which reduces the lateral swelling of the fiber in water, thereby reducing the serious fibrillation phenomenon caused by the swelling of the Lyocell fiber during the washing and friction washing process.

[0161] In summary, in combination with FE-SEM, surface Zeta potential change, and fiber surface hydrophilicity change in the figure, it can be concluded that the anti-fibrillation method of the lyocell fiber of the present invention is to adsorb cationic polymer nanospheres to the negatively charged lyocell fiber surface under the induction of electrostatic force, and when cured by high-temperature baking, the adsorbed nanospheres can be diffused into a discontinuous film, and the hydrophobic segments in the nanospheres are exposed to the air, so that the hydrophilic fiber surface is changed into a hydrophobic surface, which plays the role of the lotus effect, enhances the fiber hydrophobicity, and the swelling degree of the fiber in water is also greatly reduced. As a result, under the wet state and friction, the fibrillation tendency of the lyocell fiber is significantly suppressed.

[0162] 2. Mechanical properties of lyocell fibers in knitted fabrics:

[0163] Figure 8 It reflects the changes in the mechanical properties of Lyocell fibers before and after treatment with cationic polymer emulsion. Figure 8 It can be seen that the strength loss of the yarn before and after treatment is not large, but the elongation at break increases. This is because the nano-microspheres themselves have a soft segment structure, and a coating is formed on the fiber surface after heat treatment, making the fiber more likely to deform when subjected to external forces, increasing the elastic recovery ability of the fiber, that is, the elongation at break increases; however, high-temperature heat treatment may damage the fiber strength, or the coating and the fiber matrix are not firmly bonded, resulting in stress concentration at the interface between the coating and the matrix during stretching, thereby reducing the fiber strength. In short, the mechanical properties of Lyocell fabrics did not change much before and after treatment.

[0164] 3. About breathability:

[0165] The air permeability change test of the lyocell fabrics prepared in Example 1 and the comparative example respectively. Among them, the dry and wet air permeability tests of the lyocell fabrics prepared in the comparative example are as follows:

[0166] Table 1:

[0167]

[0168] Table 2:

[0169]

[0170] The dry and wet air permeability tests of the lyocell fabric prepared in Example 1 are as follows:

[0171] Table 3:

[0172]

[0173] Table 4:

[0174]

[0175] Tables 1 to 4 show that, compared with the original untreated pure lyocell knitted fabric, the air permeability of the fabric made after modification has increased in both dry and wet conditions, especially in wet conditions, the air permeability has increased by about 30%. This is because the swelling rate of the fabric in water after modification is reduced, resulting in a smaller fiber diameter expansion in the wet state, which in turn increases the air permeability of the treated fabric.

[0176] 4. Effect of different dosage and ratio of styrene and butyl acrylate on fibrillation effect

[0177] Example 1, Example 2, and Example 3 are the test results of Lyocell fabrics after washing after being modified with cationic polymer emulsions using the same synthesis process but with different amounts of styrene and butyl acrylate. Figure 3 , Fig. 9 and Fig.10 By adjusting different polymer ratios, from Example 1 to Example 3, as the content of styrene (hard monomer segment) in the polymer structure decreases, materials with high hardness usually have better wear resistance, because materials with high hardness can better resist deformation and wear when worn. Therefore, theoretically, the wear resistance of the polymer film formed on the fiber surface after the baking heat treatment in Examples 2 and 3 is reduced, affecting the subsequent fiber performance. Therefore, under different use requirements of fibers and fabrics, the amount and proportion of hydrophobic monomers can be reasonably selected according to actual needs.

[0178] 5. Effect of the dosage of cationic polymer nanosphere emulsion on the fibrillation effect

[0179] like Fig.11The following is a SEM image of the fabric after being treated with the anti-fibrillation treatment process of Example 4 under the condition of 40 g / L cationic polymer nanosphere emulsion and then washed with fibrillation water. Figure 3 By comparison, it can be seen that when the amount of cationic polymer nanosphere emulsion increases gradually, the fibrillation phenomenon of Lyocell fabric increases gradually. Figure 3 As shown in Example 1, when the dosage of cationic polymer nanosphere emulsion is 10 g / L, the surface of Lyocell fabric is the smoothest after fibrillation washing. Figure 3 It can be seen that the polymer film formed by the cationic polymer nanospheres spreading and solidifying on the fiber surface plays a role in subduing the giant fibrils produced on the fiber surface, so the fiber fibrillation behavior is the lightest after washing. Therefore, the preferred amount of the cationic polymer nanosphere emulsion used in the present invention is 10g / L.

[0180] 6. Effect of pH of modified treatment solution on fibrillation effect

[0181] like Fig.12 , 13 The following are SEM images of the fabric after being treated with the anti-fibrillation treatment process and then washed with water after being immersed in treatment solutions with different pH values. Figure 3 Example 1 (pH = 5), Fig.12 Example 5 (pH = 8), Fig.13 Example 6 (pH = 11). By comparison, it can be seen that as the pH value of the treatment solution gradually increases, the fibrillation phenomenon of the lyocell fabric gradually increases. As can be seen from the figure, when the pH value of the treatment solution is 5, the fiber fibrillation behavior of the lyocell fabric after the fibrillation washing is the lightest, and the performance decreases when the pH of the treatment solution is adjusted to the neutral and alkaline direction. This is because the quaternary ammonium group of the cationic polymer in the emulsion shows a strong positive charge under acidic conditions, which can generate a strong electrostatic attraction with the negatively charged lyocell fabric, while the quaternary ammonium group is more likely to react with OH under neutral and alkaline conditions. - Combined with the influence of cationic polymer emulsion nano-microspheres on the surface of lyocell fiber adsorption, spreading and film formation. Figure 3 As shown in Example 1, when the pH value of the treatment solution is 5, the surface of the Lyocell fabric is the smoothest after the fibrillation washing, and the fiber fibrillation behavior of the fabric after washing is the lightest, so the preferred pH value of the treatment solution of the present invention is 5.

[0182] About embodiment 9, the anti-fibrillation thought of the present invention is: after high temperature baking, the microsphere adsorbed on the fiber surface will melt and spread, forming a polymer film, so that the hydrophobic groups (such as benzene ring, ester group) in the microsphere internal structure are exposed, and the methyl and methylene segments in the polymer structure will also be toward the air end, and the fiber surface groups change (become hydrophobic methyl, methylene, benzene ring, ester group etc. by hydrophilic hydroxyl), so that the fiber surface as a whole presents high hydrophobicity, which will prevent water molecules from entering the fiber interior, reduce swelling, and then control the generation of fiber fibrillation. In other words, the height of hydrophobicity plays an important role in controlling the generation of lyocell fiber fibrillation. Butyl acrylate contains 4 carbon atoms in the molecular formula, and the hydrophobic part is limited, and the methacrylate octadecyl alkyl chain is longer, and it has 18 carbon atoms and then causes its hydrophobic chain to be longer than methyl methacrylate, butyl acrylate etc., and therefore has better hydrophobicity. Therefore, hydrophobic monomer styrene and butyl acrylate are replaced with methacrylate octadecyl, further improving the anti-fibrillation effect.

[0183] The invention impregnates and treats lyocell fiber by synthesizing a polyacrylate cationic polymer emulsion, and then performs the steps of baking and curing. The cationic nano-microspheres are adsorbed on the fiber surface and thermally spread to form a film, which significantly reduces the swelling degree of the fiber in water and enhances the strength of the fiber cortex, significantly improves the anti-fibrillation performance of the lyocell fiber, and maintains the good mechanical properties of the lyocell fiber. In addition, it does not cause the phenomenon of "yellowing" of the fiber and the release of formaldehyde. While improving the anti-fibrillation performance of the lyocell fabric, it does not have an adverse effect on the mechanical properties and air permeability of the fabric. In addition, the method also has the advantages of simple processing flow and low chemical consumption.

[0184] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention should fall within the protection scope of the present invention.

Claims

1. A cationic polymer nanosphere emulsion, characterized in that: It is prepared by soap-free emulsion polymerization of the following raw materials in percentage by mass:

2. The cationic polymer nanosphere emulsion according to claim 1, characterized in that: The general structural formula of the cationic polymer forming nanospheres in the emulsion is: Among them, R1 is selected from any one of benzene, acyloxymethyl, acyloxyethyl, and acyloxybutyl, R2 is selected from any one of acyloxymethyl and acyloxyoctadecyl, R3 is selected from any one of H or methyl, and R4 is selected from any one of acyloxyethyl or p-methylenebenzene.

3. The cationic polymer nanosphere emulsion according to claim 1 or 2, characterized in that: The molar ratio of the cationic monomer to the hydrophobic monomer is 1:10-210.

4. The cationic polymer nanosphere emulsion according to claim 1, characterized in that: The hydrophobic monomer is any one or more of styrene, methyl methacrylate, butyl acrylate, octadecyl methacrylate, ethyl acrylate, and methyl methacrylate; the cationic monomer is any one or more of methacryloyloxyethyl trimethyl ammonium chloride and p-vinyl benzyl trimethyl ammonium chloride; and the cationic water-soluble azo initiator is any one or two of azobisisobutylamidine hydrochloride and azobisisobutylimidazoline hydrochloride.

5. The cationic polymer nanosphere emulsion according to claim 1 or 2, characterized in that: The particle size of the cationic polymer nano-microspheres in the emulsion is 55-150nm.

6. A method for preparing the cationic polymer nanosphere emulsion according to any one of claims 1 to 5, characterized in that: The steps include: (1) Add a certain amount of deionized water into a four-necked flask equipped with a stirrer, a condenser reflux tube, and a nitrogen inlet device, and stir; (2) Add 0.2% to 2% by weight of cationic monomer into a four-necked flask and stir for 15 to 60 minutes. (3) 10% by weight of a hydrophobic monomer was added to a four-necked flask, and after sufficient stirring, the heating temperature was adjusted to 78-82°C at a heating rate of 2°C / min; (4) Add 0.02%-0.14% by weight of a cationic water-soluble azo initiator, control the drop rate, and react at 80° C. for a certain period of time to obtain a cationic polymer nanosphere emulsion.

7. Application of cationic polymer nano-microsphere emulsion in anti-fibrillation of lyocell knitted fabrics, characterized in that: The steps include:

1. Washing and degreasing of lyocell knitted fabric: (1) At room temperature, add 3-10 g / L of Dye Bath Treasure and 0.5-3 g / L of degreasing agent to deionized water and stir for 20 minutes to prepare a degreasing solution for later use; (2) Add lyocell knitted fabric, bath ratio 1:15, heat the degreasing solution at a heating rate of 5°C / min, heat to 80°C and treat for 15-60min; (3) After the degreasing solution is cooled to 40°C, take out the lyocell knitted fabric; 2. Impregnation modification treatment: (4) preparing a certain mass fraction of the cationic polymer nanosphere emulsion according to any one of claims 1 to 5 at room temperature as a modified treatment liquid for standby use; (5) immersing the lyocell knitted fabric in the cationic polymer nanosphere emulsion prepared in step (4) at a bath ratio of 1:10, adjusting the pH of the modified treatment solution to 4-11, heating the solution to 30° C., immersing the solution for 15-60 min, and then draining the solution to take out the lyocell knitted fabric; (6) dehydrating and drying the lyocell knitted fabric after the impregnation modification treatment; 3. High temperature baking treatment: (7) The lyocell knitted fabric obtained in step (6) is subjected to a high temperature baking treatment, the baking temperature is 120-180° C., and the treatment time is 5 min.

8. The use according to claim 7, characterized in that: In the step (4), the mass fraction of the cationic polymer nanosphere emulsion is 5-80 g / L.

9. The use according to claim 7, characterized in that: In the step (5), the pH of the modified treatment liquid is adjusted to 5.

10. The use according to claim 7, characterized in that: In the step (7), the baking temperature is 150°C.

Citation Information

Patent Citations

  • Fabric treatment

    CN1077184C

  • Cold pad-batch dyeing process capable of preventing fibrillation of lyocell woven fabric

    CN115772811A

  • Anti-fibrillation dipping treatment process in dyeing and finishing process of lyocell knitted fabric

    CN116716730A

  • Preparation method of pure cationic nanosphere

    CN103396505A

  • Cationic polymer emulsion for dip dyeing of coating

    CN104372690A

Cited By

  • Anti-fibrillation, dyeing and anti-ultraviolet one-bath finishing method for lyocell fibers

    CN121065969A